Access Denied - Panayides, Angelos (My University, 2020)
A. Borders (Cracks of Vanity and Cracks of Unity) Borders are agreed limitations between two or more parties, as exemplified in the geographical borders drawn as administrative boundaries between nation states. Borders can also be social and cultural, visible or invisible, real or imagined, tangible or virtual, natural or man-made. They are double faced, looking both in and out, separating and uniting as they can function both as a dividing line and as a meeting point, as an end and a beginning. We mostly structure our self-identity through borders that operate as contours of our individual/ private sphere and as interfaces with the collective/ public sphere. Borders can be respected or violated, maintained or transgressed, evolving in the constant flow of natural events and human relations. Under this category we welcome posters negotiating the aforementioned thoughts.
Keywords: triennial, poster, graphic design